Density Functional Theory Investigation on Muon Hyperfine Interaction in Methylated Guanine-Cytosine Double-Strand DNA - Jamaludin, Ammaina; Sulaiman, Shukri; Zaharim, Wan Nuradhilah; Lee Sin, Ang (Journal of Mathematical and Fundamental Sciences, 2024)
The aims of this study were to determine the most likely Mu trapping sites based on total energy consideration as well as identifying the associated muon hyperfine coupling constant of 1, 2, and 3 methylated guanine-cytosine base pair double-strand DNA. The Density Functional Theory method was used at B3LYP/6-31G level of theory to accomplish the objectives of the investigation. The relative energy in the 3 methylated guanine-cytosine base pair double-strand DNA molecule showed that N7 sites in the guanine base have the lowest energy, followed by N3, and C8 sites. It was found that the addition of a methyl group at the C5 atom in the cytosine base does change the stability of the C8 sites in the 3 methylated guanine-cytosine base pair double-strand DNA molecule, but the associated muon hyperfine coupling constant (HFCC) is not affected. The results of this study indicate that there will be no overlaps in the resonance dips due to N7, N3, and all C8 sites of the guanine bases and N3, C5, and C6 sites of the cytosine bases in the Avoided Level Crossing Muon Spin Resonance spectrum.